Mechanical properties and free formaldehyde content of particleboards produced using ammonium sulphate-based hardener partially replaced with tartaric acid : Mehanička svojstva i sadržaj slobodnog formaldehida ploča iverica izrađenih primjenom katalizatora na bazi amonijeva sulfata djelomično zamijenjenoga vinskom kiselinom - Španić, Nikola (Array, 2020)
The use of resins, whose curing reaction takes place by high temperature and hardener addition, is inevitably involved in particleboard manufacturing process. In addition to commercial hardeners, such as ammonium sulphate, with the aim of optimizing the production process and reducing the production costs, a certain percentage of hardener can, among other things, be replaced with price affordable bio-based materials. Tartaric acid, that is its salts (tartrates), which are commercially produced for the needs of wine and food industries, are a part of the aforementioned group of products. Since tartaric acid is a relatively inexpensive, readily available, weak diprotic and aldaric acid, the question arises whether it can be used as a component of the hardener system for curing urea-formaldehyde resins that are commercially used in particleboard production. For that reason, in this paper, the influence of partial replacement of ammonium sulphate hardener with tartaric acid on the mechanical properties (bending strength, modulus of elasticity and internal bond) and free formaldehyde content of experimentally produced particleboards was examined. Boards thickness, density and moisture content were also determined. The test results suggest that tartaric acid has a beneficial effect on the above particleboard properties, but they also indicate that the extent of that effect is strongly dependent on panel press time.